The influence of nuclear deformations on the probabilities of electromagnetic transitions in 1d2s-shell nuclei - Vodin, А.N.; Kopanets, Е.G.; Korda, L.P.; Korda, V.Yu. (Вопросы атомной науки и техники, 2003)
On the basis of a generalized model allowing for different deformations of a nucleus in its initial and ground states the analysis of the probabilities of electromagnetic transitions is performed. It is shown that the approach is the useful tool for investigations of the probabilities of M1 and E2 transitions between the states lying below the nucleon binding energy. The experimentally measured probabilities of M1 transitions between the analogue and anti-analogue states in the deformed 1d2s-shell nuclei are in good agreement with the calculated ones. Проведений аналіз можливостей електромагнітних переходів у рамках узагальненої моделі з урахуванням різноманітної деформації ядра в початковому і кінцевому станах. Показано, що такий підхід може служити зручним інструментом для дослідження можливостей М1- і Е2-переходів між станами, що лежать по енергії порушення нижче енергії зв'язку нуклона. Отримано гарну згоду розрахункових і експериментальних значень можливостей М1-переходів між аналоговими та антианалоговими станами в деформованих ядрах 1d2s-оболонки. Проведен анализ вероятностей электромагнитных переходов в рамках обобщенной модели с учетом различной деформации ядра в начальном и конечном состояниях. Показано, что такой подход может служить удобным инструментом для исследования вероятностей М1- и Е2-переходов между состояниями, лежащих по энергии возбуждения ниже энергии связи нуклона. Получено хорошее согласие расчетных и экспериментальных значений вероятностей М1-переходов между аналоговыми и антианалоговыми состояниями в деформированных ядрах 1d2s-оболочки.